Lysogenic Conversion of the Phytopathogen Ralstonia solanacearum by the P2virus ϕRSY1 - Askora, Ahmed; Kawasaki, Takeru; Fujie, Makoto; Yamada, Takashi (Frontiers in Microbiology, 2017)
A P2-like phage φRSY1 infecting the phytopathogen Ralstonia solanacearum was isolated and characterized. The 40-kbp genome of φRSY1 showed high sequence similarity to the Ralstonia phage φRSA1 and the GMI1000 prophage φRSX. The major genomic differences between these phages were the different orientation of the int gene and the gene content close to the cosL. φRSY1 and φRSX use a 15-base 3′ portion of the serine tRNA(GGA) gene as attB, while φRSA1 uses a 45-base 3′ portion of the arginine tRNA(CCG) gene. The different orientation of int in the genomes means that the gene arrangements in the prophage states are reversed in φRSY1 and φRSA1. Several putative gene products of φRSY1 may affect the bacteriums fitness. φRSY1 contains an ORF that seems to encode a protein similar to Vgr in the type VI secretion system of various bacterial species. φRSY1 lysogens showed phenotypic changes including enhanced twitching motility, large colony formation, and easy aggregation of cells, suggesting involvement of this ORF in the changes. In view of these phage gene arrangements, we surveyed prophages in the genomes of various R. solanacearum strains and found that the P2-like phages of R. solanacearum (14 phages) consist of two major groups: the φRSY1-type and the φRSA1-type. The relationships and evolution of these P2-like phages inferred from our data are discussed in detail.